Comparing Health Condition Between Wanted and Unwanted Pregnancy of Women in Hamadan City - Fatemeh Shobeiri; Parastoo Ahang Poor; Parisa Parsa; Saeid Yazdi-Ravandi (Hamadan University of Medical Sciences, 2019)
Introduction: Women need to be well prepared for a healthy pregnancy, childbirth, and childcare. However, confronting unplanned pregnancy and disagreement with pregnancy can cause fear, anxiety and worry during the pregnancy, and may lead to many problems for mother and baby. The aim of this study was to compare health condition between wanted and unwanted pregnancy of women under the guise of health centers in Hamadan city, Iran. Methods: This cross-sectional study is a case-control study. The statistical population of this study included all pregnant women referred to Hamadan health centers in 2016. The sample consisted of 140 people (70 cases of wanted pregnancies and 70 cases of unwanted pregnancies) referred to Hamadan health centers. After collecting data, a demographic questionnaire and a mental health questionnaire (SCL-90R) were used for data collection. The data were analyzed by descriptive statistics and t-student test and Chi-square. Two independent and single groups were analyzed. For this purpose SPSS 18 was used with a significance level of less than 0.05.  Results: The results of this study showed that there is a significant difference between obsessive-compulsive scales, physical complaints, interpersonal sensitivity, anxiety, aggression, anxiety and psyllopathy in both wanted and unwanted pregnancy groups (P<0.01). However, there was no significant difference between the result for depression in two groups of wanted and unwanted pregnancies (P>0.05). Conclusion: According to the results, it is necessary to use screening tools to diagnose mental problems, counseling and support for these women, along with the usual care during and after delivery.